A rare earth high-efficiency energy-saving heat storage material and its preparation and use method

By using rare earth high-efficiency energy-saving heat storage materials, the problem of narrow application range of existing high-temperature heat storage materials has been solved, and efficient and energy-saving heat storage effects and long service life are achieved.

CN119751128APending Publication Date: 2025-04-04BAOTOU ANDESHANAI NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411960504.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing high-temperature heat storage materials have problems such as low application temperature, high cost, low heat storage density, low heat exchange efficiency, and prone to leakage and corrosion during high-temperature phase transition, resulting in a narrow application range.

Method used

Provide a rare earth high-efficiency energy-saving heat storage material, which consists of lanthanum cerium carbonate, zircon powder, manganese dioxide, copper oxide and iron oxide. It prepares rare earth high-efficiency energy-saving heat storage powder through high-temperature sintering and grinding, and mixes it with water, dispersant, defoaming agent and binding agent to prepare rare earth high-efficiency energy-saving heat storage slurry, and is coated on the kiln heat storage body for high-temperature firing.

Benefits of technology

This material has high infrared emissivity, long-term heat storage effect, good impact resistance and corrosion resistance, which can significantly improve the heat storage growth rate and energy saving and consumption reduction effect, and extend the service life of the kiln.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751128A_ABST
    Figure CN119751128A_ABST
Patent Text Reader

Abstract

The present invention provides a rare earth high-efficiency energy-saving heat storage material and a preparation and use method thereof, which relates to the technical field of industrial kiln coatings, wherein the rare earth high-efficiency energy-saving heat storage powder is composed of the following raw materials in parts by weight: 60-85 parts of lanthanum cerium carbonate, 8-20 parts of zircon powder, 3-10 parts of manganese dioxide, 2-5 parts of copper oxide, and 2-5 parts of iron oxide. The rare earth high-efficiency energy-saving heat storage slurry is composed of the above-mentioned rare earth high-efficiency energy-saving heat storage powder, water, dispersant, defoamer and binder. The material use method includes: applying a high-temperature resistant titanium nitride isolation coating on a kiln heat storage body, then applying the rare earth high-efficiency energy-saving heat storage slurry on a high-temperature resistant titanium nitride isolation coating, and finally firing the double-coated kiln heat storage body at high temperature. The rare earth high-efficiency energy-saving heat storage material provided by the invention has a high heat storage growth rate, good energy-saving effect, reduces gas usage, reduces energy consumption, reduces carbon emissions, reduces energy costs, increases the service life of equipment and facilities, and extends the service life of the kiln.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial furnace coatings, and in particular relates to a rare earth high-efficiency energy-saving heat storage material and a preparation and use method thereof. Background Art

[0002] Industrial furnaces (hot blast furnaces, heat storage furnaces, etc.) transfer heat through the heat storage body in the heat storage chamber. The heat storage body is mainly made of porous prismatic checkerboard bricks. The checkerboard bricks are the medium for storing heat. Its heat transfer efficiency is closely related to the size, shape, and quantity of the grid holes. In the past, the thermal energy utilization rate was improved by increasing the heating area, and the material properties of the heat storage body checkerboard bricks were rarely used as a breakthrough. As the main heat storage and heat exchange element of the hot blast furnace, the heat storage capacity of the heat storage body checkerboard brick is the key to determining the thermal energy utilization efficiency.

[0003] Although there are many studies on thermal storage materials at home and abroad, the current research on high-temperature thermal storage materials is still mainly in the laboratory. At present, high-temperature thermal storage materials have more or less certain problems. Some have low application temperature; some have high cost; some have low thermal storage density; some have low heat exchange efficiency; some are prone to leakage and corrosion of equipment during high-temperature phase change; some have complex structures and other problems, resulting in a narrow range of applications. As a thermal storage material for high-temperature fields, various comprehensive performances must be considered to provide technical support for large-scale applications. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a rare earth high-efficiency energy-saving thermal storage material and a preparation and use method thereof to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the technical solution specifically adopted by the present invention is:

[0006] The first aspect of the present invention provides a rare earth high-efficiency energy-saving heat storage powder, which is composed of the following raw materials in parts by weight: 60-85 parts of lanthanum cerium carbonate, 8-20 parts of zircon powder, 3-10 parts of manganese dioxide, 2-5 parts of copper oxide, and 2-5 parts of iron oxide.

[0007] The second aspect of the present invention provides a rare earth high-efficiency energy-saving heat storage slurry, which is composed of the above-mentioned rare earth high-efficiency energy-saving heat storage powder, water, a dispersant, a defoaming agent and a binder.

[0008] As a further illustration of the present invention, the model of the dispersant is BYK190, the model of the defoamer is A10, and the binder is aluminum dihydrogen phosphate.

[0009] As a further illustration of the present invention, the mass ratio of the rare earth high-efficiency energy-saving heat storage powder, water and binder is 2:1:2; the amount of the dispersant added is 0.6% of the total mass of the heat storage slurry; and the amount of the defoaming agent added is 0.1% of the total mass of the heat storage slurry.

[0010] The third aspect of the present invention provides a method for preparing a rare earth high-efficiency energy-saving heat storage powder, comprising the following steps:

[0011] S1. Weigh the raw materials of the heat storage powder according to the above weight ratio, and then mix all the raw materials thoroughly;

[0012] S2, sintering, crushing and grinding the raw materials uniformly mixed in step S1 at high temperature to obtain rare earth thermal storage powder.

[0013] As a further illustration of the present invention, the high-temperature sintering temperature in step S2 is 1180° C., the sintering time is 3 h, the heating rate is 5° C. / min; and the grinding particle size is less than 75 μm.

[0014] A fourth aspect of the present invention provides a method for preparing a rare earth high-efficiency energy-saving thermal storage slurry, comprising the following steps:

[0015] S1, adding the rare earth high-efficiency energy-saving heat storage powder prepared by the above method, water, dispersant and defoamer, mixing and grinding to less than 10 μm,

[0016] S2. Add aluminum dihydrogen phosphate binder and stir thoroughly until there is no precipitation to obtain rare earth high-efficiency energy-saving heat storage slurry.

[0017] A fifth aspect of the present invention provides a method for using a rare earth high-efficiency energy-saving thermal storage material, comprising the following steps:

[0018] Step S1: applying a high temperature resistant titanium nitride isolation coating on a kiln heat storage body, and after standing and drying, obtaining a high temperature resistant titanium nitride isolation coating;

[0019] Step S2: coating the rare earth high-efficiency energy-saving heat storage slurry obtained above on the high-temperature resistant titanium nitride isolation coating obtained in step S1, and after standing and drying, obtaining a double-coated kiln heat storage body;

[0020] Step S3: sintering the double-coated kiln heat storage body obtained in step S2 at high temperature.

[0021] As a further explanation of the present invention, the preparation process of the high-temperature resistant titanium nitride isolation coating in step S1 is specifically as follows: titanium nitride powder, water, dispersant and defoamer are mixed and ground to less than 10 μm, and then aluminum dihydrogen phosphate binder is added and stirred until there is no precipitation to obtain a high-temperature resistant titanium nitride isolation coating; wherein the mass ratio of titanium nitride powder, water and aluminum dihydrogen phosphate binder is 2:1:2; the amount of the dispersant added is 0.6% of the total mass of the isolation coating; the amount of the defoamer added is 0.1% of the total mass of the isolation coating.

[0022] As a further illustration of the present invention, the high temperature firing system of step S3 is: heating to 1200° C. at a heating rate of 5° C. / min and firing for 3 hours, and then continuing to heat to 1500° C. and firing for 3 hours.

[0023] Compared with the prior art, the present invention has the following technical effects:

[0024] The main raw materials of the rare earth high-efficiency energy-saving heat storage powder provided by the present invention are rare earth lanthanum carbonate cerium, zircon powder, manganese dioxide, copper oxide, and iron oxide. The raw materials are widely distributed, easy to obtain, and low in cost. The prepared product has a long storage time, a low construction loss rate, good energy-saving effect, and a wear-resistant, impact-resistant, and corrosion-resistant coating, which helps to greatly reduce construction spraying losses and save costs, solves the problems of large consumption and loss during construction and elimination of unnecessary costs, and through the careful selection of the components of the rare earth heat storage auxiliary agent, the components have a significant synergistic effect, which can greatly improve the energy-saving and consumption-reducing, impact-resistant, and corrosion-resistant performance of the rare earth heat storage auxiliary agent.

[0025] The rare earth high-efficiency energy-saving heat storage material provided by the present invention has an infrared emissivity of 0.95, and a storage time extended to more than 11 days; the heat storage growth rate at 1200°C is more than 18.3%; the heat storage growth rate at 1500°C is more than 15.1%; the heat storage effect is tested in the laboratory for 120 hours without attenuation (the actual application successful case has been more than 1 year, and the heat storage energy-saving effect is still significant); it has the characteristics of wear resistance and impact resistance after passing the Class 1 immersion stripping experiment; it can be widely used to improve the heat storage rate of heat storage bodies of high-temperature kilns such as hot blast furnaces, heating furnaces, and cracking furnaces, etc., effectively reducing heat loss, saving energy and reducing consumption.

[0026] The rare earth high-efficiency energy-saving heat storage material provided by the present invention has a high heat storage growth rate, good energy-saving effect, reduces gas usage, reduces energy consumption, reduces carbon emissions, reduces energy costs, increases the service life of equipment and facilities, and extends the service life of the kiln.

[0027] The rare earth high-efficiency energy-saving heat storage material provided by the present invention can achieve the effect of energy saving and consumption reduction at 1500°C. By carefully selecting the components of the rare earth heat storage material, the components have a significant synergistic effect, which can greatly improve the energy saving and consumption reduction, impact resistance and corrosion resistance of the rare earth heat storage additive.

[0028] When the rare earth high-efficiency energy-saving heat storage slurry provided by the present invention is used, a high-temperature resistant titanium nitride isolation layer is added to block the chemical reaction between the substrate and the radiation coating (because cerium is easily oxidized from trivalent to tetravalent by oxygen in the air). The isolation layer blocks the radiation heat transfer effect, thereby having a certain effect under higher temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a flow chart of a method for preparing a rare earth high-efficiency energy-saving thermal storage material provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Table 1 Raw material information table of the following examples and comparative examples

[0032]

[0033]

[0034] Table 2 Equipment information table of the following examples and comparative examples

[0035]

[0036] Example 1

[0037] 1) Preparation of rare earth high-efficiency energy-saving thermal storage materials:

[0038] a. Preparation of rare earth high-efficiency energy-saving heat storage powder: 85 parts of lanthanum cerium carbonate, 8 parts of zircon powder, 3 parts of manganese dioxide, 2 parts of copper oxide, and 2 parts of iron oxide are fully mixed and sintered at 1180°C for 3 hours, with a heating system of 5°C / min. After sintering, the mixture is crushed and ground into 75μm to obtain rare earth high-efficiency energy-saving heat storage powder;

[0039] b. Preparation of rare earth high-efficiency energy-saving thermal storage slurry: prepare it according to the mass ratio of rare earth high-efficiency energy-saving thermal storage powder: pure water: aluminum dihydrogen phosphate = 2:1:2, first add rare earth high-efficiency energy-saving thermal storage powder, pure water, 0.6% BYK190 dispersant of the total mass of thermal storage slurry, and 0.1% A10 defoamer of the total mass of thermal storage slurry, and mix and grind them with a ball mill to less than 10μm, and the ball mill speed is above 400r / min, then add aluminum dihydrogen phosphate binder and stir it thoroughly with a disperser, and the disperser speed is above 1200r / min, stir until there is no precipitation, and obtain rare earth high-efficiency energy-saving thermal storage slurry.

[0040] 2) Heat storage growth rate test:

[0041] c. Preparation of high-temperature resistant titanium nitride isolation coating: Mix titanium nitride powder, pure water, BYK190 dispersant and A10 defoamer and grind to less than 10 μm, then add aluminum dihydrogen phosphate binder and stir thoroughly until there is no precipitation to obtain high-temperature resistant titanium nitride isolation coating; wherein the mass ratio of titanium nitride powder, water and aluminum dihydrogen phosphate binder is 2:1:2; the amount of dispersant added is 0.6% of the total mass of the isolation coating; the amount of defoamer added is 0.1% of the total mass of the isolation coating.

[0042] d. Coating sample preparation: Apply the high temperature resistant titanium nitride isolation coating on the commonly used high alumina checker brick (DRL-145), and after standing and drying, obtain the high temperature resistant titanium nitride isolation coating; then apply the rare earth high efficiency energy-saving heat storage slurry obtained above on the high temperature resistant titanium nitride isolation coating, and after standing and drying, obtain the double coating high alumina checker brick;

[0043] e. Firing: Place the double-coated high-alumina checker brick in a high-temperature furnace and heat it to 1200°C at a heating rate of 5°C / min and fire it for 3 hours, then continue to heat it to 1500°C and fire it for 3 hours;

[0044] f. Test samples of rare earth thermal storage materials: After firing is completed, the furnace temperature naturally drops to room temperature, and the fired double-coated high-alumina checker bricks are taken out to obtain test samples.

[0045] The above coating performance tests are as follows:

[0046] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coating": The heat storage growth rate of rare earth thermal storage aid test sample at 1200℃ is 18.3%, and the heat storage growth rate at 1500℃ is 15.1%; Binding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test sample passed the Class I immersion peeling test; Storage time of rare earth thermal storage aid: 20 days; Thermal storage effect time of rare earth thermal storage aid coating: 120h without attenuation.

[0047] Example 2

[0048] The difference from Example 1 is that the rare earth high-efficiency energy-saving heat storage powder is composed of the following raw materials in percentage by weight: 75 parts of lanthanum cerium carbonate, 15 parts of zircon powder, 4 parts of manganese dioxide, 3 parts of copper oxide, and 3 parts of iron oxide.

[0049] The coating performance test is as follows:

[0050] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coating": The heat storage growth rate of rare earth thermal storage aid test sample at 1200℃ is 19.9%, and the heat storage growth rate at 1500℃ is 16.2%; Binding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test sample passed the Class I immersion peeling test; Storage time of rare earth thermal storage aid: 15 days; Thermal storage effect time of rare earth thermal storage aid coating: 120h without attenuation.

[0051] Example 3

[0052] The difference from Example 1 is that the rare earth high-efficiency energy-saving heat storage powder is composed of the following raw materials in percentage by weight: 60 parts of lanthanum cerium carbonate, 20 parts of zircon powder, 10 parts of manganese dioxide, 5 parts of copper oxide, and 5 parts of iron oxide.

[0053] The coating performance test is as follows:

[0054] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coating": The heat storage growth rate of rare earth thermal storage aid test sample at 1200℃ is 21.6%, and the heat storage growth rate at 1500℃ is 17.4%; Adhesion test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test sample passed the Class I immersion stripping test; Storage time of rare earth thermal storage aid: 11 days; Thermal storage effect time of rare earth thermal storage aid coating: no attenuation after 120h.

[0055] Example 4

[0056] The difference from Example 1 is that the rare earth high-efficiency energy-saving heat storage powder is composed of the following raw materials in percentage by weight: 80 parts of lanthanum cerium carbonate, 8 parts of zircon powder, 5 parts of manganese dioxide, 4 parts of copper oxide, and 3 parts of iron oxide.

[0057] The coating performance test is as follows:

[0058] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coatings": The heat storage growth rate of rare earth thermal storage aid test samples at 1200℃ is 24.8%, and the heat storage growth rate at 1500℃ is 18.2%; Binding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test samples passed the Class I immersion stripping test; Storage time of rare earth thermal storage aid: 17 days; Thermal storage effect time of rare earth thermal storage aid coating: 120h without attenuation.

[0059] Comparative Example 1:

[0060] The difference from Example 1 is that the rare earth high-efficiency energy-saving heat storage powder is composed of the following raw materials in percentage by weight: 86 parts of lanthanum cerium carbonate, 7 parts of zircon powder, 3 parts of manganese dioxide, 2 parts of copper oxide, and 2 parts of iron oxide.

[0061] The coating performance test is as follows:

[0062] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coatings": The heat storage growth rate of rare earth thermal storage aid test samples at 1200℃ is 18.7%, and the heat storage growth rate at 1500℃ is 15.6%; Binding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test samples passed the Class I immersion peeling test; Storage time of rare earth thermal storage aid: 19 days; Thermal storage effect time of rare earth thermal storage aid coating: starts to decay after 113h.

[0063] Comparative Example 2:

[0064] The difference from Example 3 is that the rare earth high-efficiency energy-saving heat storage powder is composed of the following raw materials in percentage by weight: 59 parts of lanthanum cerium carbonate, 21 parts of zircon powder, 10 parts of manganese dioxide, 5 parts of copper oxide, and 5 parts of iron oxide.

[0065] The coating performance test is as follows:

[0066] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coatings": The heat storage growth rate of the rare earth thermal storage aid test sample at 1200℃ is 20.8%, and the heat storage growth rate at 1500℃ is 16.6%; Binding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test sample passed the Class I immersion peeling test; Storage time of rare earth thermal storage aid: 8 days; Thermal storage effect time of rare earth thermal storage aid coating: no attenuation after 120h.

[0067] Comparative Example 3:

[0068] The difference from Example 2 is that rare earth high-efficiency energy-saving heat storage powder: pure water: aluminum dihydrogen phosphate = 2:1:3.

[0069] The coating performance test is as follows:

[0070] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coating": The heat storage growth rate of rare earth thermal storage aid test sample at 1200℃ is 17.8%, and the heat storage growth rate at 1500℃ is 14.4%; Binding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test sample passed the Class I immersion stripping test; Storage time of rare earth thermal storage aid: 13 days; Thermal storage effect time of rare earth thermal storage aid coating: no attenuation after 120h.

[0071] Comparative Example 4:

[0072] The difference from Example 4 is that rare earth high-efficiency energy-saving heat storage powder: pure water: aluminum dihydrogen phosphate = 2:1:1.

[0073] The coating performance test is as follows:

[0074] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage of high-radiation coatings": The heat storage growth rate of the rare earth thermal storage aid test sample at 1200℃ is 22.5%, and the heat storage growth rate at 1500℃ is 17.1%; Bonding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test sample has poor bonding strength and is prone to peeling and falling off; Storage time of rare earth thermal storage aid: 2 days; Thermal storage effect time of rare earth thermal storage aid coating: no attenuation after 120h.

[0075] Comparative Example 5:

[0076] The difference from Example 1 is that the preparation process of the high-temperature resistant titanium nitride isolation coating is removed, and when the commonly used high-alumina checker bricks are coated, the isolation layer is not coated, and the rare earth high-efficiency energy-saving thermal storage slurry is directly coated on the commonly used high-alumina checker bricks (DRL-145).

[0077] The coating performance test is as follows:

[0078] Heat storage growth rate GB / T31934-2015 "Determination and calculation method of heat storage capacity of high-radiation coatings": The heat storage growth rate of rare earth thermal storage aid test samples at 1200℃ is 17.9%, and the heat storage growth rate at 1500℃ is 14.6%; Binding strength test GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels": The rare earth thermal storage aid test samples passed the Class I immersion peeling test; Storage time of rare earth thermal storage aid: 19 days; Time of thermal storage effect of rare earth thermal storage aid coating: It starts to decay after 87h, and the coating thickness becomes thinner, and the color gradually fades from black to lighter.

[0079] Comparing the coating heat storage effect aging index obtained by preparing the raw material composition ratio of the rare earth heat storage aid in Example 1 with the coating heat storage effect aging index obtained by preparing the raw material composition ratio of the rare earth heat storage aid in Comparative Example 1, it can be seen that when the proportion of lanthanum cerium carbonate is higher than the maximum value within the given raw material ratio range, the detected coating heat storage effect aging index decays at 113h, which is lower than the 120h of the embodiment without decay. Comparing the 1200℃ and 1500℃ heat storage growth rate indexes obtained by the ratio of rare earth heat storage aid powder: pure water: aluminum dihydrogen phosphate = 2:1:2 in the preparation of the rare earth heat storage aid in Example 2 with the ratio of rare earth heat storage aid powder: pure water: aluminum dihydrogen phosphate = 2:1:3 in the preparation of the rare earth heat storage aid in Comparative Example 3, it can be seen that after the proportion of aluminum dihydrogen phosphate is increased, the heat storage growth rates at 1200℃ and 1500℃ decrease by 2%. Comparing the storage time index obtained by preparing the raw material composition ratio of the rare earth thermal storage aid in Example 3 with that in Comparative Example 2, it can be seen that when the proportion of lanthanum cerium carbonate is lower than the minimum value within the given raw material ratio range, the detected storage time is greatly reduced to 3 days, which is much lower than the storage time of 11 days in Example 3. Comparing the storage time and bonding strength test index obtained by the ratio of rare earth thermal storage aid powder: pure water: aluminum dihydrogen phosphate = 2:1:2 in the preparation of the rare earth thermal storage aid in Example 4 with the ratio of rare earth thermal storage aid powder: pure water: aluminum dihydrogen phosphate = 2:1:1 in the preparation of the rare earth thermal storage aid in Comparative Example 4, it can be seen that after the proportion of aluminum dihydrogen phosphate is reduced, the storage time is greatly reduced to 2 days, which is much lower than the storage time of 17 days in Example 4, and peeling occurs in the bonding strength test, and the bonding strength is relatively poor. By comparing the performance test results obtained in Example 1 with those in Comparative Example 5, it can be seen that after removing the high-temperature resistant titanium nitride isolation coating, the 1200°C heat storage growth rate is not reduced too significantly, but the 1500°C heat storage growth rate is reduced by 1%, and the most serious impact is: the heat storage effect time is greatly reduced from 120h to 87h, and the coating thickness becomes thinner, and the color gradually fades from black to lighter.

[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A rare earth high-efficiency energy-saving heat storage powder, characterized in that: The invention is composed of the following raw materials in parts by weight: 60-85 parts of lanthanum cerium carbonate, 8-20 parts of zircon powder, 3-10 parts of manganese dioxide, 2-5 parts of copper oxide and 2-5 parts of iron oxide.

2. A rare earth high-efficiency energy-saving heat storage slurry, characterized in that: The invention is composed of the rare earth high-efficiency energy-saving heat storage powder as claimed in claim 1, water, a dispersant, a defoaming agent and a binder.

3. The rare earth high-efficiency energy-saving thermal storage slurry according to claim 2, characterized in that: The model of the dispersant is BYK190, the model of the defoamer is A10, and the binder is aluminum dihydrogen phosphate.

4. The rare earth high-efficiency energy-saving thermal storage slurry according to claim 2, characterized in that: The mass ratio of the rare earth high-efficiency energy-saving heat storage powder, water and binder is 2:1:2; the added amount of the dispersant is 0.6% of the total mass of the heat storage slurry; the added amount of the defoaming agent is 0.1% of the total mass of the heat storage slurry.

5. A method for preparing rare earth high-efficiency energy-saving heat storage powder, characterized in that: The following steps are involved: S1. Weigh the raw materials of the heat storage powder according to the weight ratio of claim 1, and then mix all the raw materials thoroughly; S2, sintering, crushing and grinding the raw materials uniformly mixed in step S1 at high temperature to obtain rare earth thermal storage powder.

6. The method for preparing the rare earth high-efficiency energy-saving heat storage powder according to claim 6, characterized in that: The high-temperature sintering temperature in step S2 is 1180° C., the sintering time is 3 hours, the heating rate is 5° C. / min; and the grinding particle size is less than 75 μm.

7. A method for preparing a rare earth high-efficiency energy-saving thermal storage slurry, characterized in that: The following steps are involved: S1. Add the rare earth high-efficiency energy-saving heat storage powder prepared in claim 6, water, dispersant and defoamer, mix and grind to less than 10 μm, S2. Add aluminum dihydrogen phosphate binder and stir thoroughly until there is no precipitation to obtain rare earth high-efficiency energy-saving heat storage slurry.

8. A method for using a rare earth high-efficiency energy-saving heat storage material, characterized in that: The steps include: Step S1: applying a high temperature resistant titanium nitride isolation coating on a kiln heat storage body, and after standing and drying, obtaining a high temperature resistant titanium nitride isolation coating; Step S2: coating the rare earth high-efficiency energy-saving heat storage slurry obtained in claim 7 on the high-temperature resistant titanium nitride isolation coating obtained in step S1, and after standing and drying, obtaining a double-coated kiln heat storage body; Step S3: sintering the double-coated kiln heat storage body obtained in step S2 at high temperature.

9. The method for using the rare earth high-efficiency energy-saving heat storage material according to claim 8, characterized in that: The preparation process of the high temperature resistant titanium nitride isolation coating in step S1 is specifically as follows: titanium nitride powder, water, a dispersant and a defoamer are mixed and ground to less than 10 μm, and then aluminum dihydrogen phosphate binder is added and stirred until no precipitation occurs, thereby obtaining the high temperature resistant titanium nitride isolation coating; The mass ratio of titanium nitride powder, water and aluminum dihydrogen phosphate binder is 2:1:2; the added amount of the dispersant is 0.6% of the total mass of the isolation coating; and the added amount of the defoamer is 0.1% of the total mass of the isolation coating.

10. The method for using the rare earth high-efficiency energy-saving heat storage material according to claim 8, characterized in that: The high temperature firing system of step S3 is: heating to 1200° C. at a heating rate of 5° C. / min and firing for 3 h, and then continuing to heat to 1500° C. and firing for 3 h.